Management of Dystocia Due to Posterior Presentation andUmbilical Torsion in a Jenny - Kumar, Sajjan; Singh, Jitender; Dedar, Ramesh Kumar; Thirumala Talluri (The Indian Journal of Animal Reproduction, 2024)
The present case report puts on record successful management of dystocia in a jenny suffering from posterior presentation of fetus and torsion of the umbilical cord. A five-year-old pregnant jenny in its last trimester with the history of vaginal discharges followed by mild straining without any progress was reported at the farm. The vaginal examination revealed a fully dilated cervix with the presence of a fetus with breech presentation. The fetus was relieved successfully by repulsion of the fetus, extension of flexed hind legs and final traction of the fetus without any administration of anesthesia.